Eksistensi Lembaga Penilai Dalam Pengadaan Tanah - FX. Sumarja (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: Compensation often arises in land acquisition. The purpose of this study is to determine the existence of an appraisal institution in providing an assessment of the land and/or objects that are on it, as a basis for providing reasonable compensation. The study method used in this study is normative juridical approach. The data was critically analyzed using content analysis. The results of the study indicate that the Government has established an independent institution, namely the Land Appraisal Agency, as the basis for providing compensation. The existence of an independent institution was first regulated in Presidential Regulation No. 36 of 2005. In 2012, the Land Appraisal Agency obtained a perfect regulation in a law. However, it is not automatically the only institution that has authority in valuing land prices. The government is still being halfhearted. The Land Appraisal Institution received full position in the land acquisition after the Ministerial Regulation of Agrarian & Spatial Planning/Head of National Land Agency No. 6 of 2015 was made. Intisari: Ganti rugi sering muncul dalam pengadaan tanah. Tujuan kajian ini, untuk mengetahui eksistensi lembaga penilai dalam memberikan penilaian terhadap tanah dan/atau benda-benda yang ada di atasnya, sebagai dasar memberikan ganti rugi yang wajar. Metode kajian menggunakan pendekatan yuridis normatif. Analisis data secara kritis menggunakan konten analisis. Hasil kajian menunjukkan, bahwa Pemerintah telah membentuk lembaga independen yaitu lembaga penilai pertanahan, sebagai dasar memberikan ganti rugi. Keberadaan lembaga independen pertama kali diatur dalam Peraturan Presiden No. 36 tahun 2005. Pada tahun 2012, lembaga penilai pertanahan mendapatkan pengaturan yang sempurna dalam sebuah undang-undang. Meskipun, tidak otomatis menjadi satu-satunya lembaga yang memiliki kewenangan dalam penilaian harga tanah. Pemerintah masih bersikap setengah hati. Lembaga penilai pertanahan mendapatkan kedudukan secara penuh dalam pengadaan tanah setelah adanya Peraturan Menteri Agraria & Tata Ruang/Kepala Badan Pertanahan Nasional No. 6 Tahun 2015.